Energetske potrebe človeštva skozi čas: Od industrijske revolucije do civilizacije tipa I - Kovač, Marko (Prostor, kraj, čas, 2021)
The book (' The Energy Needs Of Humanity Through Time: From The Industrial Revolution To Type I Civilization') is about global consumption of energy and its impact on our planet. Energy demand is a quite dynamic phenomenon and depends heavily on technological development, which is particularly evident during industrial revolutions, which had improved the quality of life for the inhabitants, but lead to increase in energy consumption. However~the economic progress did not account for tangible physical limits of our planet, which manifested in rise in greenhouse gas concentrations in the atmosphere and a rapid increase in average annual global temperature. The consequences of this type of behavior are clear – future global warming, rising sea levels and direct threat to vast, low-lying areas, as well as a rapid increase in the number and consequences of extreme weather events such as storms, prolonged rainfall, and the like. A path toward less energy intense future requires rapid reductions of fossil fuels usage but also a radical shift towards larger energy efficiency. The book is intended as a source of key data showing how we have arrived at the current state of energy consumption and understanding of climate change.